2012
DOI: 10.5487/tr.2012.28.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microalgal Extracts of Tetraselmis suecica against UVB-Induced Photoaging in Human Skin Fibroblasts

Abstract: Exposure of cells to ultraviolet B (UVB) radiation can induce production of free radicals and reactive oxygen species (ROS), which damage cellular components. In addition, these agents can stimulate the expression of matrix metalloproteinase (MMP) and decrease collagen synthesis in human skin cells. In this study, we examined the anti-photoaging effects of extracts of Tetraselmis suecica (W-TS). W-TS showed the strongest scavenging activity against 2,2-difenyl-1-picrylhydrazyl (DPPH) and peroxyl radicals, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
(24 reference statements)
2
19
0
Order By: Relevance
“…have potential cosmetic and pharmaceutical applications for the human hair growth and pigmentation of the skin, and also for stimulating the increased production of skin structural proteins such as filaggrin and involucrin involved in dermal diseases as Psoriasis8. In a previous study, an ethanol/water extract of Tetraselmis suecica showed a strong scavenging activity against 2,2-difenyl-1-picrylhydrazyl (DPPH) and peroxyl radicals rather than against the superoxide anions from the xanthine/xanthine oxidase system9. Here we show that a similar type of extract from T. suecica also stimulates a strong response to cell damage and activates a repairing mechanism in human epidermal cells.…”
Section: Discussionsupporting
confidence: 58%
“…have potential cosmetic and pharmaceutical applications for the human hair growth and pigmentation of the skin, and also for stimulating the increased production of skin structural proteins such as filaggrin and involucrin involved in dermal diseases as Psoriasis8. In a previous study, an ethanol/water extract of Tetraselmis suecica showed a strong scavenging activity against 2,2-difenyl-1-picrylhydrazyl (DPPH) and peroxyl radicals rather than against the superoxide anions from the xanthine/xanthine oxidase system9. Here we show that a similar type of extract from T. suecica also stimulates a strong response to cell damage and activates a repairing mechanism in human epidermal cells.…”
Section: Discussionsupporting
confidence: 58%
“…Chronic exposure to UV-B radiation typically brings about the enhanced generation of reactive oxygen species (ROS) in the skin, which leads to oxidative stress and photodamages to macromolecules, such as proteins and nucleic acids (Jo et al. 2012 ). It also causes adverse changes in the extracellular matrix that lead to skin photoaging due to the enhanced production of matrix metalloproteinases (MMPs), including MMP-1, MMP-2 and MMP-9, which is possibly mediated by augmented ROS production (Ho et al.…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione (GSH) is the primary intracellular non-enzymatic antioxidant defense against ROS and serves a central role in the reduction of oxidative stress. GPx uses GSH as a hydrogen donor to reduce H 2 O 2 and hydroperoxides to H 2 O and O 2 (35). The imbalance between antioxidants and free radicals, which is either caused by a decrease in antioxidants or an increase in ROS, leads to cell damage and cell death (36).…”
Section: Discussionmentioning
confidence: 99%